The Block Party - Day, Jamie (New York : St. Martins Press, 2023)
"The residents of the exclusive cul-de-sac on Alton Road are entangled in a web of secrets and scandal utterly unknown to the outside world, and even to each other. On the night of the annual summer block party, there has been a murder. But, who did it and why takes readers back one year earlier, as rivalries and betrayals unfold-- discovering that the real danger lies within their own block and nothing--and no one--is ever as it seems"--
Keywords: Neighborhood -- Fiction; Neighbors -- Fiction; Block parties -- Fiction; Murder -- Fiction; Secrecy -- Fiction; Interpersonal relations -- Fiction; Summer -- Fiction; Massachusetts -- Fiction; Detective and mystery fiction